Identificação de cochonilhas em cafeeiros utilizando DNA Barcoding e High Resolution Melting e distribuição potencial de Planococcus citri no Espírito Santo - Oliveira, Pablo Viana (2023)
Mealybugs (Hemiptera: Pseudococcidae) are agricultural pests of several crops, which can transmit viruses and cause great economic losses. For the control and management of these pests is essential a rapid and accurate identification of these insects. In this study, a rapid and low-cost method for identifying mealybug species was developed. The objectives are presented in the Results and Discussion section written in three chapters in Scientific Paper format. The first chapter presents an article accepted for publication in the Diversity journal, entitled "Molecular Species Delimitation Using COI Barcodes of Mealybugs (Hemiptera: Pseudococcidae) from Coffee Plants in Espírito Santo, Brazil". The dataset containing mitochondrial COI gene sequences of 26 putative of species Pseudococcidae recorded in Brazil were explored using the ASAP, GMYC, mPTP delimitation methods. An incongruence between the methods was observed, with the number of species ranging from 22 to 30 putative species. Of these, 10 species were identified among the new specimens collected in Brazil. In the second chapter, a paper to be submitted in a Journal with Impact Factor (≥ 3) is presented, entitled "Development of a High-Resolution Melting method based on COI minibarcodes to identify mealybug (Hemiptera: Pseudococcidae) pest species". A 76 bp primer pair was designed based on COI gene sequence alignment for 5 species of mealybugs. Analysis was performed by PCR immediately followed by HRM and the 5 species tested were discriminated, including two closely related species, Planococcus citri and Pl. minor. In addition, intraspecific variation was also detected in Pl. citri. The third chapter presents a paper for submission to a Journal with an Impact Factor (≥ 3), entitled "Potential distribution of the citrus mealybug, Planococcus citri (Risso, 1813), an important pest from coffee tree in Brazil”. The most abundant species found in coffee trees in Espirito Santo was chosen as a model for potential distribution prediction. Species distribution modelling was performed based on MaxEnt. North and northwest of the state was revealed to have the highest potential occurrence of this pest. This assumption was confirmed with our collection data, presented in the first chapter. This thesis presented important results on the diversity of species of mealybugs occurring in ES and another brazilian states. The tools used will help in the rapid identification of these insects and can be implemented in strategies for prophylaxis, monitoring and control of quarantine pests of agricultural crops in Brazil and other countries.